2016
DOI: 10.1002/cssc.201600904
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphene Aerogels Decorated with Cobalt Phosphide Nanoparticles as Electrocatalysts for the Hydrogen Evolution Reaction

Abstract: The development of non-precious-metal hydrogen evolution reaction (HER) electrocatalysts with high activity and excellent durability in acidic media is of significant importance for renewable energy research. We report a novel electrocatalyst based on a three-dimensional (3D) graphene aerogel decorated with cobalt phosphide nanoparticles (CoP/GA). The material has a unique hierarchical porous structure with CoP nanoparticles encapsulated uniformly within the graphene sheets. The optimized catalyst shows superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Graphene can not only prevent the aggregation of the TMPs, but also interconnect the separate nanoparticles to improve the charge transfer kinetics and structural stability through facilitating electrons transfer. Therefore, graphene‐based composite exhibits enhanced catalytic activities for HER . For example, Ma et al reported the fabrication of CoP nanoparticles deposited on reduced graphene oxide sheets to enhance electrocatalytic activity for the HER .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene can not only prevent the aggregation of the TMPs, but also interconnect the separate nanoparticles to improve the charge transfer kinetics and structural stability through facilitating electrons transfer. Therefore, graphene‐based composite exhibits enhanced catalytic activities for HER . For example, Ma et al reported the fabrication of CoP nanoparticles deposited on reduced graphene oxide sheets to enhance electrocatalytic activity for the HER .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, graphene-based composite exhibits enhanced catalytic activities for HER. [6,8] For example, Ma et al reported the fabrication of CoP nanoparticles deposited on reduced graphene oxide sheets to enhance electrocatalytic activity for the HER. [9] Jiao et al developed CoP/rGO composites as superior bifunctional catalysts for overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…So far, little attention have demonstrated that incorporation of transition metals (e. g., Mn, Al and Ni) into CoP, could enhance catalytic activity by altering the crystal lattice and bond length to modify the free energy of hydrogen adsorption on catalyst surface . Besides, other studies are implying that hybridization of CoP and nanocarbon materials such as graphene oxide, graphene, carbon nanotubes and porous carbon derived by metal‐organic frameworks (MOFs), are alternative way to increase the conductivity of the catalysts . Although, recent studies are highlighted that CoP encapsulated nitrogen doped carbon based nanohybrid catalysts are significantly improve the catalytic activity compared than carbon coated CoP counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…

In this communication, the urchin-like Te template is obtained by photo-assisted electro-deposition to replace trace platinum, gold and rhodium to obtain the Pt@Te-PsS, Au@Te-PsS and Rh@Te-PsS catalysts in pursuit of their highly efficient utilization. [4][5][6][7][8] Nevertheless, their scarcity, high cost and weak stability impede their large-scale industrial application. Moreover, the electrons of Te are delocalized, to increase the electron density of interface and promote the hydrogen evolution reaction.

…”
mentioning
confidence: 99%